Lactate dehydrogenase as surrogate marker of preeclampsia and eclampsia - Vidhya, Muthuramalingam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy is a spectrum of disorder which include chronic hypertension that antedates pregnancy and gestational hypertension or pre-eclampsia that is unique to human pregnancy. It is still a poorly understood condition. The clinical course is progressive and characterized by continuous deterioration that is arrested only by termination of pregnancy. Hence the disease must be detected in early stage and managed appropriately for improved maternal and fetal outcome. Methods: The study consists of 173 antenatal patients of gestational age 28 weeks and above. Study population was divided into two groups, Group 1 consists of 50 antenatal women of normotensive nature served as controls and group 2 consists of 123 antenatal women with confirmed hypertension. Venous blood samples were collected used for the estimation of lactate dehydrogenase enzyme. Results: Out of the total 173 patients 104 women delivered by C-section, 67 by normal vaginal delivery and 2 by assisted breech delivery. Among the women who delivered by caesarean 60 (57.69%) had serum LDH less than 600, 18 (17.30%) had serum LDH between 600 and 800 and 26 (25.00%) had LDH above 800. Among the women who delivered vaginally 61 (91.04%) had LDH less than 600, 1 (1.49%) had LDH between 600 and 800 and 5 (7.46%) had LDH above 800. Only 2 women delivered by assisted breech delivery one with LDH between 600 and 800 and another with S. LDH above 800. Conclusions: The study was done in search of a valuable marker for preeclampsia and Eclampsia which would reflect the severity of the disease and would predict the maternal and fetal outcome. Such markers can help in decision making and can influence the current management protocols in order to achieve a better maternal and perinatal outcome.